(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article analyzes legal regulation and some procedural aspects of accepting a plea deal in U.S. criminal proceedings. The authors considered the procedural procedure, the parties, the content of the plea deal, the procedure for approving it, the legal consequences of the implementation of the legal institution of the plea deal.